2018
DOI: 10.1164/rccm.201802-0215oc
|View full text |Cite|
|
Sign up to set email alerts
|

Azithromycin for Early Pseudomonas Infection in Cystic Fibrosis. The OPTIMIZE Randomized Trial

Abstract: Azithromycin was associated with a significant reduction in the risk of pulmonary exacerbation and a sustained improvement in weight, but had no impact on microbiological outcomes in children with early Pa. Clinical trial registered with clinicaltrials.gov (NCT02054156).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(58 citation statements)
references
References 46 publications
1
55
0
Order By: Relevance
“…Most recently, azithromycin reduced the time to next exacerbation in young children with CF who developed newly identified P aeruginosa in respiratory cultures. It did not reduce the risk of developing chronic P aeruginosa infection or the time to next acquisition of P aeruginosa …”
Section: Cellular Contributions To the Cf Airway Inflammatory Responsementioning
confidence: 92%
See 1 more Smart Citation
“…Most recently, azithromycin reduced the time to next exacerbation in young children with CF who developed newly identified P aeruginosa in respiratory cultures. It did not reduce the risk of developing chronic P aeruginosa infection or the time to next acquisition of P aeruginosa …”
Section: Cellular Contributions To the Cf Airway Inflammatory Responsementioning
confidence: 92%
“…It did not reduce the risk of developing chronic P aeruginosa infection or the time to next acquisition of P aeruginosa. 183 Regardless of the mechanism(s) of action, the proven clinical benefits of chronic azithromycin in the CF population have resulted in widespread use. According to the CFFPR, nearly 70% of those with chronic P aeruginosa infection are prescribed this therapy in the United States.…”
Section: Azithromycinmentioning
confidence: 99%
“…In our study, improved weight gain was noted with nebulized azithromycin. Weight gain associated with azithromycin has been reported (26,27). Mayer-Hamblett et al evaluated the effects of addition of oral azithromycin to inhaled tobramycin as eradication regimen of new PA (26).…”
Section: Discussionmentioning
confidence: 99%
“…Weight gain associated with azithromycin has been reported (26,27). Mayer-Hamblett et al evaluated the effects of addition of oral azithromycin to inhaled tobramycin as eradication regimen of new PA (26). The authors observed decreased pulmonary exacerbations and increased weight in the azithromycin group.…”
Section: Discussionmentioning
confidence: 99%
“…Azithromycin is widely used in people with CF, but its effects are still being characterized. The OPTIMIZE (Optimizing Treatment for Early Pseudomonas aeruginosa Infection in Cystic Fibrosis) trial was a multicenter, double‐blind, randomized, placebo‐controlled, 18‐month trial in children with CF, 6 months to 18 years of age, with early PA respiratory tract infection . Early infection was defined as a documented new positive oropharyngeal, sputum, or lower‐respiratory‐tract culture for PA within 40 days of the baseline visit, which was either the first lifetime documented PA‐positive culture or PA recovered after at least 2 years of PA‐negative cultures with at least one culture documented per year.…”
Section: Pulmonary Healthmentioning
confidence: 99%